Sustained Liver Glucose Release in Response to Adrenaline Can Improve Hypoglycaemic Episodes in Rats under Food Restriction Subjected to Acute Exercise - Lucas K. R. Babata; Maria M. D. Pedrosa; Rosângela F. Garcia; Márcia V. Peicher; Vilma Aparecida Ferreira de Godoi (International Journal of Endocrinology)
Background. As the liver is important for blood glucose regulation, this study aimed at relating liver glucose release stimulated by glucagon and adrenaline to in vivo episodes of hypoglycaemia. Methods. The blood glucose profile during an episode of insulin-induced hypoglycaemia in exercised and nonexercised male Wistar control (GC) and food-restricted (GR, 50%) rats and liver glucose release stimulated by glucagon and adrenaline were investigated. Results. In the GR, the hypoglycaemic episodes showed severe decreases in blood glucose, persistent hypoglycaemia, and less complete glycaemic recovery. An exercise session prior to the episode of hypoglycaemia raised the basal blood glucose, reduced the magnitude of the hypoglycaemia, and improved the recovery of blood glucose. In fed animals of both groups, liver glucose release was activated by glucagon and adrenaline. In fasted GR rats, liver glycogenolysis activated by glucagon was impaired, despite a significant basal glycogenolysis, while an adrenaline-stimulated liver glucose release was recorded. Conclusions. The lack of liver response to glucagon in the GR rats could be partially responsible for the more severe episodes of hypoglycaemia observed in vivo in nonexercised animals. The preserved liver response to adrenaline can partially account for the less severe hypoglycaemia in the food-restricted animals after acute exercise.